Sistem Inventarisasi dan Eksplorasi Pertambangan Batu Bara Di Kalimantan Berbasis Mobile Android - Fauzan Anwari Alkhasani; Fatwa Ramdani; Aryo Pinandito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT Britmindo is a mining company that provides reliable reports and solutions for the various services required by coal mine owners. One solution done in the framework of efficiency in the field of mining is to utilize Geographic Information System (GIS) at the exploration stage. Currently PT Britmindo provides a website-based system that can be utilized for exploration and inventory activities. However, the use of sparate digital cameras and GPS handheld in the inventory takes a lot of time when adding inventory results into the system whereas website-based concession maps are less than optimal when accessed through smartphones that are easy to carry in exploration activities. From these problems, a system of coal mining inventory and exploration in Kalimantan based on Android mobile is developed by utilizing GPS and camera features on smartphone, where users can view location concession maps and make inventory through geotagging and tracking. Inventory and exploration system was developed with waterfall model. The results of this study is an Android-based mobile applications. Testing on this system using validation testing, user acceptance testing (UAT) and usability testing where the results of testing validation testing and usability testing resulted in the conclusion that the system is 100% valid and very easy to use, while the results of UAT testing resulted in conclusion that the system has been in accordance with user needs.